Forecasting the herbal usage value at Ban Bong Tai Sub-district Health Promoting Hospital, Sakon Nakorn - Thatasuk, Jitlada; Jayathavaj, Vadhana; Khamprore, Sakhon; Khanthong, Phaksachiphon (UBRU Journal for Public Health Research, 2025)
This descriptive study aimed to predict herbal medicine expenditures for the fiscal year 2024 using a model based on Grey System Theory. Secondary data were obtained from herbal medicine expenditure records for fiscal years 2017 to 2023, covering a total of seven years, at Ban Bong Tai Subdistrict Health Promoting Hospital, Bong Tai Subdistrict, Sawang Daen Din District, Sakon Nakhon Province. The data were analyzed using quantitative forecasting techniques, specifically time-series models. Model accuracy was validated using the Mean Absolute Percentage Error (MAPE). An analysis of herbal medicine expenditure over the past eight fiscal years revealed that in 2016 the expenditure was more than twice that of other years; therefore, this outlier was excluded from further analysis. Applying the GM (1,1) model of Grey System Theory, the predicted expenditure for 2024 was estimated with a MAPE of 20.26 percent, indicating a satisfactory level of forecasting accuracy. The forecasted expenditure for 2024 is 229,323, representing an estimated 38.48 percent increase from 2023. This projection is consistent with the observed pattern, which displayed a saw-tooth trend of increases and decreases, with a decline in 2023 following an increase in 2022. The findings suggest that Ban Bong Tai Subdistrict Health Promoting Hospital can utilize these predictive data to ensure adequate supplies of frequently prescribed herbal medicines, thereby supporting effective operations within the local community.